Can encapsulation of the biocide DCOIT affect the anti-fouling efficacy and toxicity on tropical bivalves? - Dos Santos, Juliana Vitoria Nicolau [UNESP]; Martins, Roberto; Fontes, Mayana Karoline [UNESP]; de Campos, Bruno Galvão [UNESP]; E Silva, Mariana Bruni Marques Do Prado [UNESP]; Maia, Frederico; Abessa, Denis Moledo de Souza [UNESP]; Perina, Fernando Cesar [UNESP] (MDPI, 2020)
The encapsulation of the biocide DCOIT in mesoporous silica nanocapsules (SiNC) has been applied to reduce the leaching rate and the associated environmental impacts of coatings containing this biocide. This research aimed to evaluate the effects of DCOIT in both free and nanostructured forms (DCOIT vs. SiNC-DCOIT, respectively) and the unloaded SiNC on different life stages of the bivalve Perna perna: (a) gametes (fertilization success), (b) embryos (larval development), and (c) juveniles mussels (byssus threads production and air survival after 72 h of aqueous exposure). The effects on fertilization success showed high toxicity of DCOIT (40 min-EC50 = 0.063 µg L−1), followed by SiNC-DCOIT (8.6 µg L−1) and SiNC (161 µg L−1). The estimated 48 h-EC50 of SiNC, DCOIT and SiNC-DCOIT on larval development were 39.8, 12.4 and 6.8 µg L−1, respectively. The estimated 72 h-EC50 for byssus thread production were 96.1 and 305.5 µg L−1, for free DCOIT and SiNC-DCOIT, respectively. Air survival was significantly reduced only for mussels exposed to free DCOIT. Compared to its free form, SiNC-DCOIT presented a balanced alternative between efficacy and toxicity, inhibiting efficiently the development of the target stage (larvae that is prone to settle) and satisfactorily preventing the juvenile attachment.
Keywords: Biofouling; Nanotechnology; Perna perna; Toxicity